Characters versus letters: ideography and morphology in Chinese - Garrido, Joaquín (Círculo de Lingüística Aplicada a la Comunicación, 2018)
This article analyzes the two official Chinese letter and character writing systems, and the ideographic conception of characters, in terms of the morphological and phonological properties underlying the two systems. It is argued that (i) letters in 拼音 pīnyīn are phonemic and (ii) characters 汉字 hànzì are morphemic. Ideography or the ideographic conception of characters as representing ideas is then shown to be wrong, since characters represent morphemes, and today they represent the Chinese language, that is, 普通话 pǔtōnghuà “the common language” or 汉语 hànyǔ “Chinese”. “Mandarin” or 官话 guānhuà, “officials’ language” is therefore an incorrect name for “the Northern language” 北方话 Běifānghuà. Characters are used to represent other Chinese languages such as Cantonese, 粤语 yuèyǔ, as well as the Japanese language, and they have been used to represent Vietnamese and Korean. Contrary to ideography’s tenets, it is shown that the character 汉字 writing system, a fundamental part of Chinese culture in itself, today represents morphemically the Chinese language, and the letter writing system pīnyīn represents Chinese phonemically.